Who is Focusing on Women’s Health: A Bibliometric Analysis of Global Research Trends on Overweight in Female Patients with Gynecologic or Breast Cancer - Gu J; Zhang H; Qian K; Ye X; Wu G (International Journal of Women's Health)
Jialin Gu,1,* Hongqun Zhang,2,* Kang Qian,1 Xunwen Ye,3 Guolin Wu1 1Department of TCM, The First Affiliated Hospital of Zhejiang University School of Medicine, Hangzhou, Zhejiang, 310003, People’s Republic of China; 2Hunan Engineering Research Center of TCM Real-World Clinical Practice, The First Affiliated Hospital of Hunan University of Medicine, Huaihua, Hunan, 418000, People’s Republic of China; 3Department of Oncology, Ningbo Municipal Hospital of Traditional Chinese Medicine, Affiliated Hospital of Zhejiang Chinese Medical University, Ningbo, Zhejiang, 315500, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guolin Wu, Department of TCM, The First Affiliated Hospital of Zhejiang University School of Medicine, Hangzhou, Zhejiang, 310003, People’s Republic of China, Email wuguolin28@163.comObjective: Obesity has become a significant public health concern, strongly linked to various diseases, particularly gynecologic and breast cancers. This bibliometric review aims to analyze global research trends on overweight women, particularly those with gynecologic and breast cancers, to identify research hotspots, key contributors, and emerging areas of study.Methods: A comprehensive bibliometric analysis was conducted using the Web of Science Core Collection (WoSCC) database, covering the period from January 2013 to September 2024. Articles were screened and analyzed using tools such as VOSviewer and Biblioshiny platform, with metrics including publication volume, citation analysis, and co-authorship networks. Key areas of focus were global research trends, leading countries, institutions, authors, journals, and keyword analysis.Results: A total of 1452 publications were analyzed. Research activity on the association between obesity and gynecologic/breast cancer has steadily increased, with the United States leading in publications and citations, followed by China and Italy. Core journals included Breast Cancer Research and Treatment and Gynecologic Oncology. Key research areas identified through keyword analysis include the relationship between body mass index (BMI) and cancer risk, survival rates in cancer patients, physical activity, and the role of adipose tissue inflammation in tumor progression. Emerging topics include extracellular vesicles and cancer-associated fibroblasts.Conclusion: Global research on the relationship between obesity and female-specific cancers has shown significant growth. The findings highlight BMI, survival, and physical activity as central themes. Future research should explore the molecular mechanisms linking obesity to cancer and evaluate weight loss interventions for cancer prevention and treatment.Keywords: obesity, gynecologic cancer, breast cancer, bibliometrics, women health